Analyzing Impact of Computer Attacks on the Banking System of the Russian Federation - A. A. Salcutan (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article analyzes damage caused by attacking finance organizations in the Russian Federation through activization of hacker groups. The mentioned attacks were mainly directed at banking cards’ processing, cash machines and the SWIFT system, an international system of transmitting finance information and payments. The growth in hacker penetrations can be seen in all sectors of Russian economy, it is based on informational confrontation and aims at destabilization of considerable objects of critical information infrastructure. Today special attention is paid to attacks of hacker groups, which get financing from states and criminal groupings in order to exert influence on the leading banks of the world. The author investigated the key methods of attacks of finance organizations. The role of the Federal service on technical and export control and the Department of information security of the Bank of Russia was described. By assessing the impact of computer attacks the author came to the conclusion that the Russian banking sector is vulnerable to computer attacks on informational systems that could cause damage not only to small but also big credit organizations, which possess over 60% of the Russian banking sector assets.